Newer‐generation antihistamines and the risk of adverse events in children: A systematic review. Issue 7 (20th May 2021) - Miligkos, Michael; Dakoutrou, Maria; Statha, Eleni; Theochari, Nikoletta A.; Mavroeidi, Ilektra Antonia; Pankozidou, Ιoanna; Papaconstadopoulos, Irene; Papadopoulos, Nikolaos G.
Abstract: Background: H1‐antihistamines (AHs) are widely used for the treatment of allergic diseases, being one of the most commonly prescribed classes of medications in pediatrics. Newer‐generation AHs are associated with fewer adverse effects compared with first‐generation AHs. However, their relative harms in the pediatric population still need scrutiny. Methods: We performed a systematic review of randomized controlled trials (RCTs), which included comparisons of safety parameters between an orally administered newer‐generation AH and another AH (first‐ or second‐generation), montelukast, or placebo in children aged ≤12 years. We searched MEDLINE and CENTRAL, independently extracted data on study population, interventions, adverse events (AEs), and treatment discontinuations, and assessed the methodologic quality of the included RCTs using the Cochrane's risk of bias tool. Results: Forty‐five RCTs published between 1989 and 2017 met eligibility criteria. The majority of RCTs included school‐aged children with allergic rhinitis and had a follow‐up period of up to a month. Four RCTs reported serious AEs in patients receiving a newer‐generation AH, but only two patients experienced a possibly drug‐related serious AE. The occurrence of AEs, drug‐related AEs, and treatment discontinuations due to AEs varied between RCTs. Most AEs reported were of mild intensity. Indirect evidence indicates that cetirizine is more sedating than the other newer‐generation AHs. Conclusion: Our findings confirm that newer‐generation AHs have a favorable safety and tolerability profile. However, we could not draw firm conclusions regarding the comparative safety profile of the newer‐generation AHs due to the paucity of head‐to‐head RCTs, variation in definitions and reporting of AEs, and short follow‐up duration.